Color Concept of Dewata Nawa Sanggha in Barong Ket Mask - Asthararianty Asthararianty; Imam Santosa; Irfansyah Irfansyah; I Nyoman Larry Julianto (Institute of Research and Community Outreach - Petra Christian University, 2026)
The Barong Ket Mask is a famous mask in Bali. As a traditional Balinese visual artifact, it has a distinctive visual character in its shape and color. The color concept of Dewata Nawa Sanggha is a Balinese Hindu symbolic color system associated with the cardinal directions, gods, and symbolism in the Barong Ket Mask. This research is a literature and conceptual study that maps the application of the color concept of Dewata Nawa Sanggha and analyzes the symbolic meaning of color through Roland Barthes's semiotics. It uses a qualitative methodology, including a literature review and visual semiotics. Data will be collected from books, journals, and other publications. Data analysis uses Roland Barthes's visual semiotics to interpret denotation, connotation, and myth. The result is a mapping of the Dewata Nawa Sanggha color concept onto the colors of the Barong Ket Mask, forming a structured symbolic visual system. The colors red, white, black, gold, pink, and their gradations are associated with the color concept of Dewata Nawa Sanggha and serve as symbolic visual media that represent identity, protection, and cosmological meaning. This research provides a conceptual foundation for further studies.